(untitled) (Research, Society and Development, 2020)
The aim of the present work was to analyze the structural properties of germinated adzuki bean flour at different germination stages. Germination was conducted with four replications of 50 seeds and germination was performed at 6, 8, 10 and 12 days, considering protrusion or root size as an indicator of germination. To obtain the flour, germinated adzuki beans were placed in trays and placed in a drying oven at a temperature of 50 °C and an air velocity of 1.0 m.s-1 until constant mass; X-ray diffraction analyzes and Fourier transform infrared spectroscopy were performed in the formulations. All samples were classified as crystallinity type A and showed an increase in the degree of crystallinity according to germination time. The structure of molecules of germinated adzuki bean flour was modified according to germination time and root size. Differences in intensity were observed in diffractograms and spectrograms, in the latter no different peak was verified by prolonged germination.